نظام إدارة البلديات المختلطة في الجزائر خلال العهد الاستعماري وانعكاساته على بعض بلديات الجنوب القسنطيني - حليسي,علي; بلفردي,جمال (University of Eloued جامعة الوادي, 2024)
الملخص تناولنا في ثنايا هذا المقال الهياكل التنظيمية الفرنسية في البلديات المختلطة في الجنوب القسنطينيّ بلديتي المسيلة وأريس" خلال الفترة 1947- 1870 ، والذي مرّ بثلاث مراحل وفق التنظير الإداري الاستعمار الفرنسي الذي لم يجد من حيلة إدارية إلاّ وحاول اسقاطها على الحقل التجريبي له والمتمثل في المجتمع الجزائري، فمن مفهوم العرش والقبيلة إلى الدواوير وصولا إلى الخرائط الجغرافية والإدارية المركزية كلها تجليات للمفهوم الإداري الذي سلط لغاية دقيقة مراقبة الأهالي والتحكم في تنقلاتهم ظاهريا، والهدف المحوري التحكم في جباية الضرائب من هؤلاء المقهورين من الجزائريين خدمة لسياسة الاستيطاني والفصل العنصري، وهذا ما جاد به صاحبا المقال في مستواه الأول، وفي النسق الثاني له حاولا فيه سرد ونقد الانعكاسات السلبية المترتبة عن تلك السياسة على سكان الجنوب القسنطيني في البلديات محل الدراسة، خاصة مع كثرة التأويلات الإدارية في إقرار المنظومة القانونية العنصرية الفرنسية، والممارسات التعسفية، واستغلال كل ما يملكه الجزائري لصالح المشروع الاستيطاني الفرنسي " إدارة، ومعمرين". This article deals with the French organisational structures in the mixed municipalities of southern Constantine, Msila and Arris, during the period 1947-1947, which went through three stages according to the administrative theorisation of French colonialism, which did not find any administrative trick but trying to project it onto its experimental field, namely Algerian society, from the concept of the throne and the tribe to the rural villages to the geographical and central administrative maps, all of which are manifestations of the administrative concept that was used for the precise purpose of monitoring the population and controlling their movements, ostensibly with the central objective of controlling the collection of taxes from these oppressed Algerians in order to serve the policy of settlement. This is what the authors argued in the first level of the article, and in the second, they tried to list and criticise the negative repercussions of this policy on the inhabitants of southern Constantine in the municipalities studied, especially with the many administrative interpretations of the French racist legal system, arbitrary practices, and the exploitation of everything owned by Algerian citizen in favour of the French settlement project (administration and colonisers).
المسيلة، آريس أنموذجا 1870- 1947
Keywords: آريس; المسيلة; الجنوب القسنطيني; العهد الاستعماري; البلديات المختلطة; Arris; M’Sila; Mixed Municipalities; Southern Constantine; Colonial Era